Heart failure in the child and young adult : from bench to bedside - Jefferies, John Lynn; Chang, Anthony C.; Rossano, Joseph W.; Shaddy, Robert E.; Towbin, Jeffrey A. (Academic Press, an imprint of Elsevier, 2018)
This book combines multiple etiologies for pediatric heart failure, including congenital heart disease, cardiomyopathies, infectious diseases, and metabolic abnormalities, and includes research and current guidelines for the recognition and management of heart failure in children. Coverage includes the basic science of heart failure, diagnosis, management, treatment and surgery, and advanced special topics, such as genetics, self-management and nanomedicine.